1989
DOI: 10.1148/radiology.173.3.2813770
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis: diagnostic value of three-dimensional CT reconstruction.

Abstract: Three-dimensional computed tomography (CT) has an important role in determining the presence and extent of congenital and acquired craniofacial deformities. The authors compared the sensitivity and specificity of three-dimensional CT in the detection and characterization of craniosynostosis with that of planar CT and skull radiography. Eighty-two patients with isolated and syndromal synostoses were imaged with CT and three-dimensional CT, and 42 with skull radiography. Three-dimensional CT scan processing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(47 citation statements)
references
References 0 publications
1
40
0
6
Order By: Relevance
“…5,24 At the same time, radiologists began reinterpreting plain films and using computed tomography to determine the correct diagnosis. [25][26][27] Furthermore, clinical studies showed that deformational plagiocephaly could be corrected by positioning in the crib and use of a molding helmet. [3][4][5] In fact, the incidence of true lambdoid synostosis is very rare (Ͻ4% of craniosynostosis).…”
mentioning
confidence: 99%
“…5,24 At the same time, radiologists began reinterpreting plain films and using computed tomography to determine the correct diagnosis. [25][26][27] Furthermore, clinical studies showed that deformational plagiocephaly could be corrected by positioning in the crib and use of a molding helmet. [3][4][5] In fact, the incidence of true lambdoid synostosis is very rare (Ͻ4% of craniosynostosis).…”
mentioning
confidence: 99%
“…These patients also underwent surgery to relieve the narrowing of the superior orbital fissures and optic foramina. 3-D CT imaging in congenital and developmental craniofacial anomalies is important in the pre-operative evaluation and therapy planning than in diagnosis and the results are much better than plain radiographs and 2-D CT scans [5].…”
Section: Discussionmentioning
confidence: 99%
“…Já foi demonstrado como um instrumento válido e reprodutível para fornecer dados objetivos do formato craniano. Importante considerar ainda que mesmo sendo rotineira a obtenção do perímetro cefálico para acompanhamento clinico, a fita métrica não pode ser usada como critério diagnóstico das assimetrias cranianas, uma vez que as mesmas medidas podem ser obtidas em diferentes formatos cranianos 12,14,17 .…”
Section: Introductionunclassified